Normativismo y antinormativismo en la tradición gramatical española del siglo XVII - Martínez Gavilán, María Dolores (1990)
The first romance grammars came forth from the humanist' desire to grant a similar prestige to the vernacular languages as was possessed by the classical languages with the idea that the perfection of a language is measured by its capacity to be subjected to grammar regulation or codification. The problem of determining the level of usage -literary, cultivated, common-that provides the base for the foundation of the grammatical system of language, requires in each country its own characteristics as a consequence of its specific linguistic, historical, and cultural circumstances. In the light of this problem, this paper will examine the peculiarity of the Spanish grammatical tradition opposite to the rest of the European traditions and, fundamentally, will analyze the solutions that were adopted on the decisive norm-usage question for the Spanish grammar of the 17th century.
Keywords: Gramática -- 1601-1700; Lengua española -- Normalización -- 1601-1700